The Decommissioning of Offshore Oil and Gas Installations and Structures in Nigeria and South Africa in the context of international best practices - West, Soalabo (Institute of Marine and Environmental Law, 2014)
This work attempts to examine the laws relating to the decommissioning of offshore oil and gas installations and structures in Nigeria and South Africa, in the context of international best practices as typified by the regimes in operation in Norway and the United Kingdom. The extent to which these countries have met their obligations under international law will also be considered; being that states' liberty to design their laws applicable to the continental shelf and exclusive economic zone is limited by their obligations under international law.